Replacing key employee retention plans with incentive plans in bankruptcy - Capkun, Vedran; Ors, Evren (Accounting, Organizations and Society, 2021)
We examine executive bonus contracts in corporate bankruptcies. Introduced in 2005, Section 503(c)(1) of the United States' Chapter 11 corporate bankruptcy code regulates key employee retention plans (KERPs) but does not restrict performance incentive plans (PIPs). We find that, following the adoption of this reform, the likelihood of approval of KERPs and their coverage decrease, while those of PIPs increase. Unintended consequences of the reform include lower operating performance for PIPs and decreases in reorganization efficiency for bankrupt firms adopting KERPs or PIPs. Our results are consistent with the idea that KERPs were rent-extraction tools, which contrasts with prior evidence. PIP pay-performance link weakens after the reform, due to an increase in adoption of zero-performance thresholds and more discretion given to debtors over bonus pay. This suggests that watering down of PIPs' incentives may have re-introduced the rent extraction that the reform sought to eliminate. We conclude that the regulation of bonuses in bankruptcy should consider debtors’ reactions to such reforms.